European guidelines on perinatal care- Peripartum care Episiotomy. (12th December 2022) - Laine, Katariina; Yli, Branka M.; Cole, Vanessa; Schwarz, Christiane; Kwee, Anneke; Ayres-de-Campos, Diogo; Vayssiere, Christophe; Roth, Emmanuel; Gliozheni, Elko; Savochkina, Yuliya; Ivanisevic, Marina; Kalis, Vladimir; et al.
SUMMARY OF RECOMMENDATIONS: 1. Episiotomy should be performed by indication only, and not routinely (Moderate quality evidence +++-; Strong recommendation) . Accepted indications for episiotomy are to shorten the second stage of labor when there is suspected fetal hypoxia (Low quality evidence ++–; Weak recommendation) ; to prevent obstetric anal sphincter injury in vaginal operative deliveries, or when obstetric sphincter injury occurred in previous deliveries (Moderate quality evidence +++-; Strong recommendation) 2. Mediolateral or lateral episiotomy technique should be used (Moderate quality evidence +++-; Strong recommendation) . Labor ward staff should be offered regular training in correct episiotomy techniques (Moderate quality evidence +++-; Strong recommendation) . 3. Pain relief needs to be considered before episiotomy is performed, and epidural analgesia may be insufficient. The perineal skin needs to be tested for pain before an episiotomy is performed, even when an epidural is in place. Local anesthetics or pudendal block need to be considered as isolated or additional pain relief methods (Low quality evidence ++–; Strong recommendation) . 4. After childbirth the perineum should be carefully inspected, and the anal sphincter palpated to identify possible injury (Moderate quality evidence +++-; Strong recommendation) . Primary suturing immediately after childbirth should be offered and a continuous suturing technique should be used when repairing an uncomplicated episiotomy (High quality evidence ++++; Strong recommendation)